Development of Instruments to Measure Self-Confidence and Creative Thinking in Mathematics Learning for Vocational High School Students (Universitas Negeri Semarang, 2022)
This study was a Research and Development that aimed to develop in order to gain a standard instrument for measuring self-confidence and creative thinking in mathematics learning. The instrument for measuring self-confidence and creative thinking in the mechanical engineering expertise program used the development of test and non-test instruments. This study uses a large scale with a total of 210 students of class X (Vocational High School) SMK Negeri 1 Lambu Bima District. The research used an instrument development model that used a test and a non-test Mardapi Theory with 10 steps. The ten steps of developing this instrument produce a valid and reliable instrument product, simplified into three steps. There were a preliminary stage, development stage, and evaluation stage. The preliminary stage consists of determining the specifications of the writing of the instrument and determining the scoring. The development stage consists of instrument review by an expert. testing. analysis. and revision. The evaluation stage consists of assembling and refining the instrument. The validity and content reliability analysis used the Aiken formula and the Hoyt formula for construct validity using Exploratory Factor Analysis (EFA) and reliability using Cronbach’s Alpha. Based on the results of research in the field the measuring instrument for self-confidence and creative thinking is said to be valid and reliable. It has a value of 0.3 with an average of 0.747. The conclusion of the research: the instrument is feasible to use. While the contribution of this research is this instrument can measure the increase of self-confidence and creative thinking in mathematics learning.